An action research on improving the electronic records management of Accounting Department in Philippine Deposit Insurance Corporation - Anyayahan, Noreen F. (Animo Repository, 2017)
This Action Research aimed to improve the electronic records management of Accounting Department in Philippine Deposit Insurance Corporation to address the lack of having a centralized filing system of electronic files which we found out to be the cause of our Department's most common issue of having difficulty in locating electronic files and its most updated version. Addressing this underlying issue, discarded the waste of time locating a particular file and helped address other issues related to accessing, securing, and sharing of files, hence, improved the Departments efficiency and productivity. We were able to cover two full cycles of Action Research. Different tools and methods such as 5 Whys technique, the Scheins three types of inquiry process, focus group discussion, informal conversations and one on one meeting were used to discuss the issues and identify the focal issue. The use of tools such as ORJI, journaling, and ladder of inference were also useful in doing this Action Research. All throughout the action research project, collaboration with the Departments personnel was done to come up with the best possible solution to resolve the identified issue. We adopted the use of theories related to the issue and Xiaomi Ans Best-Practice Framework of Integration for Managing Electronic Records in planning for the activities and interventions for this Action Research. In our first intervention, we agreed to prepare a User Account Maintenance Form to be forwarded to IT for the request of having a Shared Drive facility for exclusive use of Accounting Department personnel and prepared guidelines in the set-up of the Drive. As a result of the evaluation of our first intervention, we concurred to have guidelines in managing and organizing of files stored in the Drive to avoid the issues related to mismanaged files and ensure the sustainability of our change initiative and considered the idea of strengthening the back-up of the Drive which can help maximize the benefits of the Drive in our second intervention. Through the implementations of the two interventions, we are able to attain the set objectives of this Action Research and at the same time achieve other positive outcomes as discussed in the latter parts of this paper.